THE CORRELATION BETWEEN EXPOSURE TO SHORT-FORM CONTENT ON TIKTOK AND INSTAGRAM REELS AND EFL LISTENING SKILLS AMONG HIGH SCHOOL STUDENTS - Hamdan Syakirin Hamid, Faishal; Angelaila Fauzi, Florence; Hafizah, Azizatun; Syahid, Abdul (JIPIS, 2025)
AbstractThis study examines the impact of short-form content on TikTok and Instagram Reels on the English as a Foreign Language (EFL) listening skills of high school students. Employing a quantitative correlational research design, the study involved 30 participants who completed pre-tests and post-tests to measure their listening comprehension. Data collection included a questionnaire capturing usage patterns of TikTok and Instagram Reels and a listening comprehension test using TED-Ed videos. The analysis revealed that short-form content positively correlates with improved listening skills, suggesting that these platforms offer engaging and interactive learning opportunities. However, the study also highlighted potential challenges, such as content quality and distraction risks. These findings provide valuable insights for educators and policymakers to leverage digital platforms effectively in EFL instruction, balancing their potential benefits with strategies to address associated challenges.Keywords: digital platforms; EFL; Instagram Reels; listening skills; short-form content; TikTok